Opportunities to Talk Matter in Shared Reading: The Mediating Roles of Children’s Engagement and Verbal Participation in Narrative Listening Comprehension - Lepola Janne; Kajamies Anu; Laakkonen Eero; Collins Molly (Routledge, Taylor Francis Group, 2025)
Research Findings: The present study examined children’s listening comprehension during a two-semester-long dialogic reading. We explored the extent to which the development of children’s listening comprehension was accounted for by initial listening comprehension and whether children’s engagement and the amount and level of their verbal participation in shared reading contributed to their later listening comprehension. The opportunities provided by teachers, such as closed and open-ended questions were also examined. A total of 60 five-year-old children participated in 15 story groups. Children’s listening comprehension was evaluated twice. Teachers rated the children’s behavioral and cognitive engagement. Children’s verbal participation and the teachers’ questions were observed directly. A theoretical model involving direct and indirect pathways in the development of listening comprehension was analyzed. Path modeling showed that the children’s cognitive engagement and the amount of verbal participation mediated the development of individual differences in listening comprehension. Additionally, teachers’ open-ended questions contributed indirectly to listening comprehension via children’s verbal participation. Practice or Policy: The findings highlight the benefits of children’s active participation in discussions and talk-intensive reading aloud for their story comprehension.